PSYCHOLOGICAL TRANSFORMATION OF INDONESIAN VOCATIONAL EFL LEARNERS THROUGH SELF-DIRECTED LEARNING: A CASE STUDY ON SPEAKING PROFICIENCY - Nozylianty Nozylianty; M Bambang Purwanto; Muhammad Rifqi; Yusri Yusri; Vivin Afini (Jurnal Pendidikan Teknologi dan Kejuruan, 2026)
This study aims to analyze the effectiveness of self-directed learning (SDL) in enhancing the speaking skills of EFL students, as well as to identify the psychological transformations that occur during the learning process. The research involved 40 grade XI students majoring in Hospitality and Tourism at SMK Negeri 3 Palembang who were being prepared for internship programs and the world of work. Using a sequential explanatory mixed-methods design, quantitative data were obtained through pre-test and post-test speaking ability assessments, while qualitative data were collected through semi-structured interviews. The results of the quantitative analysis showed a significant increase in the speech ability score, from an average of 58.45 in the pre-test to 76.10 in the post-test, with values of t = -20.59 and p = 0.000, indicating the substantial effectiveness of the SDL intervention. Qualitative findings further confirm that independent practice, facilitated through voice recording, simulated dialogue, and self-reflection, can increase self-confidence, reduce anxiety, and foster learning independence. The integration of the two findings shows that SDL not only improves linguistic performance but also has a positive impact on students' psychological readiness for authentic communication in the hospitality and tourism industry